PONTIANAK BASKETBALL ARENA - Patuhrahman, Muhammad Arief; Lestari, Lestari; Irwin, Irwin (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
The development of basketball in Pontianak City is in line with the availability of basketball sports facilities owned. Existing facilities are still inadequate or do not meet standards. Based on this phenomenon, the goal to be achieved in designing the Pontianak Basketball Arena is to produce a type A basketball sports building design in Pontianak City. This design refers to the Instruction Manual for Technical Planning for Sports Buildings published by the Ministry of the Public Works (1994) and Minister of Youth and Sports of the Republic Indonesia Number 0445 of 2014 concerning Standards for Sports Infrastructure in the Form of Buildings and using the design method proposed by Jones (1992), where the method is divided into several stages, namely the idea stage, problem identification stage, data collection stage, data analysis stage, synthesis stage, and design stage. This design gave a building divided into 2 floors. The square shape of the building was chosen because it is considered to be the most suitable shape according to the land site and also be the most efficient shape according to the room organization. The facade of the building displays a shape inspired by the patterns found in basketball and the culture that exist in the city of Pontianak. The colors in the building are contrasted to create a prominent feel to make it more attractive and sporty. The space frame structure system applied to the roof of the building was chosen based on several considerations.